Determination of basal ileal endogenous losses and standardized ileal digestibility of amino acids in barley fed to growing pigs. Issue 1 (December 2016) - Spindler, Hanna; Mosenthin, Rainer; Rosenfelder, Pia; Jørgensen, Henry; Bach Knudsen, Knud; Eklund, Meike
Abstract Background Basal ileal endogenous amino acid (AA) losses (IAAend ) and standardized ileal digestibility (SID) values of cereal grains, such as barley, are apparently underestimated when determined according to the nitrogen (N)-free method. Regression analysis between the dietary apparent ileal digestible content (cAID) and total crude protein (CP) and AA can be considered as alternative approach to obtain more accurate values for IAAend and SID of AA in cereal grains. Methods Eight hulled barley genotypes were used, with barley being the only source of CP and AA in the assay diets. The diets contained 95 % as-fed of these eight barley genotypes each, ranging in CP content between 109.1 and 123.8 g/kg dry matter (DM). Nine ileally T-cannulated barrows, average body weight (BW) 30 ± 2 kg, were allotted to a row-column design comprising eight periods with 6 d each and nine pigs. On d 5 and the night of d 6 of every period, ileal digesta were collected for a total of 12 h. The IAAend and the SID were determined by linear regression analysis between cAID and total dietary CP and AA. Results There exist linear relationships between cAID and total CP and AA (P < 0.001). The IAAend of CP, Lys, Met, Thr and Trp amounted to 35.34, 1.08, 0.25, 1.02 and 0.38 g/kg DM intake (DMI), respectively, which are greater compared to average IAAend determined previously under N-free feeding conditions. The SID of CP, Lys, Met, Thr and Trp was 90, 79, 85, 79 and 86 %, respectively, and was greater when compared to tabulated values. Moreover, these SID values were greater than those reported in literature, based on correction of apparent ileal digestibility (AID) of CP and AA for their IAAend values. Summarized, the results of the present regression analysis indicate greater IAAend in barley-based diets compared to those obtained by N-free feeding. Conclusions For low-protein feed ingredients like barley the regression method may be preferred over correction of AID values for their IAAend determined under N-free feeding conditions, as intercepts and slopes of the linear regression equations between cAID and total dietary CP and AA provide direct estimates of IAAend and SID of CP and AA in the presence of the assay feed ingredient.